What Alice forgot [compact disc, unabridged] - Moriarty, Liane (Penguin Audio, 2011)
Alice Love drifts out of a dream to find herself in unfamiliar surroundings. But real life quickly becomes a nightmare when she discovers that nothing is as she remembers, and the last 10 years of her memory have vanished.